Isotope effect on hydrogen bond symmetrization in hydrogen and deuterium fluoride crystals by molecular dynamics simulation. Issue 6 (25th January 2019) - Dammak, Hichem; Brieuc, Fabien; Geneste, Grégory; Torrent, Marc; Hayoun, Marc
Abstract : We evidence the symmetrization of the H-bonds occurring in HF and the deuteron hopping in DF through the tunnel effect. Abstract : The isotope effect on the collective proton/deuteron transfer in hydrogen and deuterium fluoride crystals has been investigated at 100 K by ab initio quantum-thermal-bath path-integral molecular dynamics (QTB-PIMD) simulation. The deuterons within a planar zigzag chain of the orthorhombic structure simultaneously flip between covalent and hydrogen bonds due to the barrier crossing through tunnelling. The height of the corresponding static barrier normalized for one deuteron is 29.2 meV. In the HF crystal, all the protons are located at the center of the heavy-atom distance. This evidences the symmetrization of the H-bonds, and indicates that the proton zero-point energy is above the barrier top. The decrease of the heavy-atom distance due to quantum fluctuations in both HF and DF crystals corresponds to a large decrease and an increase of the hydrogen and covalent bond lengths, respectively. Upon deuteration, the increase of the heavy-atom distance (Ubbelohde effect) is in agreement with experimental data.